Parallel Solver of Large Systems of Linear Inequalities Using Fourier-Motzkin Elimination - Šimeček, Ivan; Fritsch, Richard; Langr, Daniel; Lórencz, Róbert (Computing and Informatics, 2017)
Fourier-Motzkin elimination is a computationally expensive but powerful method to solve a system of linear inequalities. These systems arise e.g. in execution order analysis for loop nests or in integer linear programming. This paper focuses on the analysis, design and implementation of a parallel solver for distributed memory for large systems of linear inequalities using the Fourier-Motzkin elimination algorithm. We also measure the speedup of parallel solver and prove that this implementation results in good scalability.